Embeddings of (proper) power graphs of finite groups - Doostabadi, A.; Farrokhi D.G., M. (Algebra and Discrete Mathematics, 2017)
The (proper) power graph of a group is a graph whose vertex set is the set of all (nontrivial) elements of the group and two distinct vertices are adjacent if one is a power of the other. Various kinds of planarity of (proper) power graphs of groups are discussed.